PENGARUH TEKNIK RELAKSASI HYPNOBIRTHING TERHADAP PENURUNAN RASA NYERI KALA I PERSALINAN DI PRAKTIK MANDIRI BIDAN (PMB) SITI SARA, S.Tr.Keb KECAMATAN IDI TUNONG KABUPATEN ACEH TIMUR - Riska Nisfi Fitria; Rahmisyah Rahmisyah; Ully Muzakir (Universitas Bina Bangsa Getsempena, 2023)
The birth process is a series of events that begin with the expulsion of a full-term or nearly full-term baby accompanied by the expulsion of the placenta and fetal membranes from the birth canal. Almost all women experience and feel pain during labor, but each woman's response to labor pain is different. Various efforts have been made to reduce labor pain, both pharmacologically and non-pharmacologically. One of the non-pharmacological methods that can be used to reduce labor pain is hypnobirthing. The purpose of this study was to determine the effect of hypnobirthing relaxation techniques on reducing pain in the first stage at Siti Sarah's Independent Midwife Practice (PMB). S.Tr.Keb, Idi Tunong District, East Aceh Regency. This type of research is